Applying Lessons from Athletic Recruitment to Faculty Searches - David M Bellar; Peter Sheppard (Academic Chairpersons Conference Proceedings, 2017)
The presenter will share how lessons learned from recruiting intercollegiate athletes can be applied to faculty searches. The presentation will present information and examples for improving position announcements as well as interactions and negotiations with candidates to increase the likelihood of a quality hire.
Keywords: Faculty; Recruitment; Search; Hiring; Position Announcement